2014
DOI: 10.1161/circresaha.114.301763
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1 Mediates C-Reactive Protein–Evoked Endothelial Vasodilator Dysfunction in Coronary Arterioles

Abstract: I nflammation-related cardiovascular disturbance is regarded as a pivotal event in the development of atherosclerosis. 1 C-reactive protein (CRP), a biomarker of inflammation and cardiovascular deterioration, is becoming an emerging risk factor for cardiovascular disease. The landmark Justification for the Use of statins in Prevention: an Intervention Trial Evaluating Rosuvastatin (JUPITER) study recently showed that statin therapy significantly reduced the CRP levels, along with the incidence of major cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…The sLOX-1 level, however, may be a better parameter than hs-CRP to differentiate the LVH+ patients from the LVH- patients based on the ROC curves. These experimental results correlate to close functional partnership of LOX1 and CRP that has been well studied in their pro-atherogenic effects on vascular cells [16,38,39,40,41]. Among all, a recent study suggested that L5, a subfraction of plasma LDL, CRP and the LOX-1 may constitute a positive feedback loop that contributes to endothelial dysfunction [39].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The sLOX-1 level, however, may be a better parameter than hs-CRP to differentiate the LVH+ patients from the LVH- patients based on the ROC curves. These experimental results correlate to close functional partnership of LOX1 and CRP that has been well studied in their pro-atherogenic effects on vascular cells [16,38,39,40,41]. Among all, a recent study suggested that L5, a subfraction of plasma LDL, CRP and the LOX-1 may constitute a positive feedback loop that contributes to endothelial dysfunction [39].…”
Section: Discussionsupporting
confidence: 59%
“…LOX-1 along with Fcγ receptors functions as a receptor for CRP [42]. CRP elicits oxidative stress and compromises vasomotor function on porcine coronary arterioles via LOX-1 activation [38]. In addition, CRP promotes the release of soluble LOX-1 from macrophages by activating tumor necrosis factor alpha (TNF-α) converting enzyme [39] and increases vascular permeability through direct binding to LOX-1[42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that CRP increases vascular permeability through a direct interaction with LOX-1 dependent on calcium that can be outcompeted with phosphorylcholine (3 ). In addition, CRP induces monocyte-endothelial cell adhesion through LOX-1 (8 ) and impairs endotheliumdependent vasodilator function through LOX-1 (30 ). Furthermore, Fujita and colleagues (31 ) have shown in hypertensive rats that LOX-1 is also involved in CRPinduced complement activation, whereby LOX-1 may have a role in tethering CRP to the cell membrane to induce complement activation.…”
Section: Biologic Interactions Of Crp Lox-1 and Atherogenic Ldlmentioning
confidence: 99%
“…2). Although Fc␥Rs were initially postulated to mediate the effects of CRP outside of complement activation, evidence has indicated that both LOX-1 and Fc␥Rs mediate some effects of CRP (30 ). Importantly, OxLDL and plasma L5 isolated from hypercholesterolemic patients have been shown to induce the release of CRP from human aortic endothelial cells in a LOX-1-dependent manner, whereas native LDL has no effect (32,33 ).…”
Section: Biologic Interactions Of Crp Lox-1 and Atherogenic Ldlmentioning
confidence: 99%